Safeguarding intangible cultural heritage - Stefano, Michelle L.; Davis, Peter, 1947 November 15-; Corsane, Gerard, 1962- (Heritage matters series, 2012)
Wide-ranging essays on intangible cultural heritage, with a focus on its negotiation, its value, and how to protect it.